Vitamin D and the insulin‐like growth factor system: Implications for colorectal neoplasia. (24th May 2020) - Ciulei, George; Orasan, Olga Hilda; Coste, Sorina Cezara; Cozma, Angela; Negrean, Vasile; Procopciuc, Lucia Maria
Abstract: Epidemiological studies have strongly associated lower levels of vitamin D and its metabolites with an increased risk of colorectal cancer (CRC). The action of calcitriol, the active metabolite of vitamin D, is mediated by the vitamin D receptor (VDR) that is present in most tissues. In advanced CRC, VDR expression is lowered. Calcitriol has several antineoplastic effects in CRC: it promotes the G1‐phase cycle arrest, lowers vascular endothelial growth factor (VEGF) synthesis and acts on tumour stromal fibroblasts to limit cell migration and angiogenesis. Hyperinsulinemia and insulin‐like growth factors (IGFs) have been implicated in the pathophysiology of CRC. IGF‐1 and IGFBP‐3 have been the most studied components of the IGF system. Only 1% of the total serum IGF‐1 is free and bioactive, and 80% of it binds to IGFBP‐3. IGF‐1 and its receptor IGF‐1R are known to induce cell proliferation. Both IGF‐1 and IGFBP‐3 can favour angiogenesis by increasing the transcription of the VEGF gene. A high serum IGF‐1/IGFBP‐3 ratio is associated with increased risk for CRC. VDR is a transcription factor for the IGFBP‐3 gene, and IGF‐1 can increase calcitriol synthesis. Studies examining the effect of vitamin D treatment on serum IGF‐1 and IGFBP‐3 have not been in agreement since different populations, dosages and intervention periods have been used. New vitamin D treatment studies that examine CRC should take in account confounding factors such as obesity or VDR genotypes.